Turkish National Security Strategy Towards Iraq after 2011: Objectives and Means - Azad Salih Othman; Beastun Omer Nuri (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Since 2011 the Arabic region, including Iraq, has been witnessing a wave of changes, which have affected the deterioration of the political, economic, security, and social conditions, and are reflected in changing the geostrategic power in the region. There is an opportunity for regional powers to impose their hegemony and review their strategies to achieve their higher goals. In the framework of these changes, Turkey has changed its security strategy orientation towards the region in general and Iraq, in particular, to protect its interests and achieve its higher goals, because Iraq is in the midst of events. Because of the proximity of the geographical borders and the importance of the location of Iraq, these changes directly affect Turkey’s national security. In order to reach its strategic objectives in Iraq, it reformulated its security strategy towards Iraq and ensured the territorial integrity of Iraq. In order to ensure the safety of national security and achieve its goals in Iraq, such as containing the future of the Kurdish entity in Iraq, increasing its influence in Iraq and benefiting from Iraqi economic resources, and to achieve these goals, it relied on several means such as the army, Turkmen parties, intelligence and media.